Оптимальное управление нормализацией энергетического баланса клетки - Атоев, К.Л. (Теорія оптимальних рішень, 2006)
The tasks of energetic balance normalization and systemic risks minimization for cell are investigated. The conditions of metastable chaos arising in cellular energetic system are determined.